Wen-Xin Decoction ameliorates vascular endothelium dysfunction via the PI3K/AKT/eNOS pathway in experimental atherosclerosis in rats. Issue 1 (December 2015) - Li, Tongda; Li, Dongmei; Xu, Hui; Zhang, Huamin; Tang, Danli; Cao, Hongxin
Abstract Background Nitric oxide (NO) is the most powerful vasodilator that inhibits leukocyte adhesion, platelet aggregation, and vascular smooth muscle cell proliferation. However, excessive NO can cause lipid peroxidation and direct endothelial cell damage. Therefore, investigation of the role of NO in artherosclerosis development is important. Wen-Xin Decoction (WXD) has been shown to relieve myocardial ischemia reperfusion injury and prevent leukocyte adhesion and invasion; in addition, it can accelerate angiogenesis and prevent platelet activation and aggregation. In this study, we focused on the NO pathway to further clarify the protective effects of WXD on the vascular endothelium in rat models of artherosclerosis. Methods Wistar rats were randomly divided into a normal group (n  = 10) and a model group (n  = 75). Rat models of atherosclerosis were generated by intraperitoneal vitamin D3 (3 months) injections and administration of a high-fat diet (3 months with vitamin D3 and 2 months alone). The model rats were randomly divided into five groups (n  = 15 each): model (saline), atorvastatin (4.8 mg/kg/d atorvastatin), high-dose WXD (9 g/kg/d), medium-dose WXD (4.5 g/kg/d), and low-dose WXD (2.25 g/kg/d) groups. Each group received continuous drug or saline administration (suspended liquid gavage) for 30 days, following which all animals were sacrificed. The ultrastructure and histopathological changes of vascular endothelial cells and the expression of PI3K/AKT/eNOS and iNOS in the thoracic aorta tissue were analyzed. Results WXD increased NO levels, modulated the NO/ET-1 ratio, and promoted repair of the injured vascular endothelium in a dose-dependent manner. At a high dose, WXD regulated the NO/ET-1 ratio as effectively as atorvastatin; furthermore, it increased NO levels within the physiological range to prevent endothelial damage caused by excessive NO expression. Real-time polymerase chain reaction and Western blot analysis showed that WXD significantly upregulated the mRNA and protein expressions of PI3K, AKT, and eNOS mRNA and significantly increased AKT and eNOS phosphorylation. Conclusions Our results suggest that WXD protects and maintains the integrity of the vascular endothelium by activating the PI3K/AKT/eNOS pathway, decreasing iNOS expression, and promoting the release of physiological NO levels.